Reference and Representation in Translation: a Look Into the Translator's Resources - Shakir, Abdullah (Meta)

(untitled) (Les Presses de l'Université de Montréal, 1995)
AbstractThis study investigates the effect of schematic knowledge on the appropriateness and communicative acceptability of the translation rendered of four ambiguous contextless texts. The four texts (a road sign and three advertisements) were translated in two separate sessions by twenty-eight students pursuing a B.A. in English language and literature. In the first session, the students were provided with the texts decontextualized: while in the second they were provided with the same texts in the contexts they usually occur in. In the two sessions the students were asked to explain in a separate sheet why thev translated each text in the way they did. Two notions, closely related to the translating process, are discussed in the analysis of the translation provided. These notions are "reference" and "representation". The analysis has shown that the student translators resorted to referential strategies in the process of translating when they were aware of the relevant contextual dimensions of the target text. Their translations in this case retained the registral, rhetorical, and formal characteristics of the types of texts they translated. The analysis has also shown that when unaware of the pertinent contextual dimensions of the text, the student translators resorted to representational (introspective) strategies whereby contexts and world realities deriving from experiences and worlds other than those intended by the SL text producer were created, and the translations bore rhetorical, registral, and syntactic features relevant to the contexts and world realities the translators created.